2012
DOI: 10.1093/jxb/ers002
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana proliferating cell nuclear antigen has several potential sumoylation sites

Abstract: Proliferating cell nuclear antigen (PCNA) is post-translationally modified in yeast and animal cells. Major studies carried out in the last decade have focused on the role of sumoylated and ubiquitinated PCNA. Using different approaches, an interaction between plant PCNA and SUMO both in vivo and in bacteria has been demonstrated for the first time. In addition, identical sumoylation patterns for both AtPCNA1 and 2 were observed in bacteria. The plant PCNA sumoylation pattern has been shown to differ significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 52 publications
1
26
1
Order By: Relevance
“…Immobilized metal ion affinity chromatography (IMAC) is a simple and a fast technique which has been successfully used for the purification of many recombinant proteins, produced in bacteria [1][2][3], yeast [4,5], mammalian cells [6,7] and insect cells [8,9], under either native or denatured conditions. This method is based on the reversible interaction between the histidine tag (His-tag), which is attached either at the N-or C-terminus of the purified protein, and divalent metal ions, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Immobilized metal ion affinity chromatography (IMAC) is a simple and a fast technique which has been successfully used for the purification of many recombinant proteins, produced in bacteria [1][2][3], yeast [4,5], mammalian cells [6,7] and insect cells [8,9], under either native or denatured conditions. This method is based on the reversible interaction between the histidine tag (His-tag), which is attached either at the N-or C-terminus of the purified protein, and divalent metal ions, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Selected combinations of PCNA1, PCNA2 and CycA1 (BiFC control) fused with full length, N-terminal or C-terminal GFP fragments were transiently overexpressed in Nicotiana benthamiana epidermal cells. 21,26 The results of this…”
mentioning
confidence: 98%
“…[19][20][21][22] One of the broadly studied PCNA post-translational modifications is ubiquitination. 20,22 The stalled replication forks induce PCNA ubiquitination at lysine 164 and activate postreplication repair.…”
mentioning
confidence: 99%
“…It is also of great interest to notice that in a reported in vitro assay, AtPCNA can be ubiquitinated in the presence of Ubc2 (Rad6) but absence of any E3 [11]. Furthermore, the same group also reported that the AtPCNA-K164R mutant proteins can still be ubiquitinated [11] or sumoylated [10], raising a possibility that AtPCNA1-K200 and AtPCNA2-K262 may serve as alternative residues for PCNA covalent modifications in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…Although the molecular mechanisms of DDT are thought to be conserved in plants [6][7][8][9], and AtPCNA can be sumoylated [10] and ubiquitinated [11] in vitro, the involvement of plant PCNA in DDT has not yet been demonstrated in vivo. The Arabidopsis genome encodes two PCNAs differing in only nine amino acid residues (Fig.…”
Section: Introductionmentioning
confidence: 99%